1983
DOI: 10.1113/jphysiol.1983.sp014658
|View full text |Cite
|
Sign up to set email alerts
|

Strength and cross‐sectional area of human skeletal muscle.

Abstract: SUMMARY1. The maximum voluntary force (strength) which could be produced by the knee-extensor muscles, with the knee held at a right angle, was measured in a group of healthy young subjects comprising twenty-five males and twenty-five females. Both legs were tested: data from the stronger leg only for each subject were used in the present study.2. Computed tomography was used to obtain a cross-sectional image of the subjects' legs at mid-thigh level, measured as the mid-point between the greater trochanter and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

28
381
5
10

Year Published

1993
1993
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 624 publications
(432 citation statements)
references
References 21 publications
28
381
5
10
Order By: Relevance
“…A similar gender difference in fiber number was observed in the tibialis anterior (Henriksson-Larsen 1985). A number of investigators have reported that the strength/GSA ratio is greater in males than in females (Morris 1948;Young et al 1985;Ryushi et al 1988), however, considerable variation exists within each gender (Maughan et al 1983;Maughan & Nimmo). Differences in limb lengths (McCullagh et al 1984) and the connective tissue volume density (Sale et al 1987) probably account for some of the variability in the strength/GSA ratio between and within genders.…”
Section: 3 Fiber Numbermentioning
confidence: 99%
See 2 more Smart Citations
“…A similar gender difference in fiber number was observed in the tibialis anterior (Henriksson-Larsen 1985). A number of investigators have reported that the strength/GSA ratio is greater in males than in females (Morris 1948;Young et al 1985;Ryushi et al 1988), however, considerable variation exists within each gender (Maughan et al 1983;Maughan & Nimmo). Differences in limb lengths (McCullagh et al 1984) and the connective tissue volume density (Sale et al 1987) probably account for some of the variability in the strength/GSA ratio between and within genders.…”
Section: 3 Fiber Numbermentioning
confidence: 99%
“…The finding that strength and muscle cross-sectional area (GSA) are highly correlated (Ikai & Fukunaga 1968;Maughan et al 1983;Maughan & Nimmo 1984) and that the strength to GSA ratio is similar for males and females (Ikai & Fukunaga 1968;Schantz et al 1983;Sale et al 1987) …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of nonferromagnetic titanium prostheses and ceramic balls instead of metal heads, as well as the observances of some technical features, eg, the orientation of the frequency-encoding gradient of the MR system, enables high-quality MRI of patients with THA. The changes in muscle cross-sectional area (CSA) and fatty atrophy of the muscle that can thus be visualized reflect the muscle damage and correlate with muscle function [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…IF THE STRENGTH of a muscle is to be properly related to its size, the physiological cross-sectional area (CSA) should be measured (1). In vivo, the physiological CSA of a muscle is linearly correlated with its volume (2,3), so a volumetric assessment will offer a surrogate measure of physiological significance.…”
mentioning
confidence: 99%